Valuing the Attribute Enhancements of Urban Park: A Case of the King Rama IX International Mangrove Botanical Garden, Thailand - Laksanacom, Aekkapat; Seenprachawong, Udomsak (Journal of Applied Economics and Management Strategy, 2023)
The King Rama IX International Mangrove Botanical Garden (The King Rama IX-IMBG), Thailand provides a bundle of benefits, including a source for exchanging knowledge on mangrove forests and recreation opportunities. This study was applied a choice experiment to investigate the potential users’ preferences and willingness to pay for different educational programs and recreational enhancement projects in The King Rama IX-IMBG, Thailand. The population used in this study were tourists between the ages of 20 and 60 who had experience in traveling to provinces in the Eastern region. The sample size was determined using the ratio of 40 samples per choice set. There are 10 choice sets for this study, thus estimating the optimal sample size of 400 individuals who were determined by purposive sampling. The empirical results from conditional logit model show the potential users are willing to pay 25 Baht, 27 Baht, 89 Baht, and 102 Baht for improved museum design, information signs, recreation activities, and facilities, respectively. The results suggest that the planning and management of this place subject to budget constraints should take into account the attributes of this botanical garden and the preferences of visiting citizens to improve their welfares.